1975
DOI: 10.1039/f19757101083
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic properties of the calcium + calcium chloride system measured by an electrochemical technique

Abstract: A galvanic cell study of the Ca+CaC12 system is reported. By proper allowance for electronic conduction in the electrolyte phase, the thermodynamic properties have been determined. These data are in good agreement with a vapour pressure study and phase diagram determinations. A model is proposed based upon non-stoichiometric compound theory involving an electron pair exchange equilibrium (Ca2)2+ +2CaZ+ + e2 at low Ca concentration. As the Ca concentration approaches saturation, electron pairs are increasingly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 1 publication
2
29
0
Order By: Relevance
“…Although the CaO saturation is about 20 mol% CaO in CaO-CaCl 2 binary system [20][21][22], it was reported that it took longer time to achieve equilibrium at higher CaO concentration [25,31]. When the concentration of CaO in the bath is high, the larger current can be supplied; the larger amount of Ca is generated per unit time as explained in section 3.1.…”
Section: Reduction At Cacl 2 -50 Mol%caomentioning
confidence: 99%
See 1 more Smart Citation
“…Although the CaO saturation is about 20 mol% CaO in CaO-CaCl 2 binary system [20][21][22], it was reported that it took longer time to achieve equilibrium at higher CaO concentration [25,31]. When the concentration of CaO in the bath is high, the larger current can be supplied; the larger amount of Ca is generated per unit time as explained in section 3.1.…”
Section: Reduction At Cacl 2 -50 Mol%caomentioning
confidence: 99%
“…This implies that the rate of reduction was faster at the higher CaO concentration, probably because the larger amount of CaO in the melt was consumed for electrolysis and the larger amount of Ca for reduction is being generated in a short period. Slight decrease in the rate of current decline at 5.0 mol% CaO may be due to the possible precipitation of liquid Ca metal because molten CaCl 2 can only dissolved up to 4 mol% Ca [23][24][25][26][27][28] and this value decreased with small addition of CaO in the bath [31]. The microscopic oxygen distribution was tried to be measured by SEM equipped with energy dispersive X-ray (EDX) detector, but the precise profiles were not detected because of light nature of oxygen.…”
Section: Concentration Dependency Of the Currentmentioning
confidence: 99%
“…(3) dissolves in the CaCl 2 melt, because the solubility of Ca is reported as about 4 mol%Ca [13][14][15][16][17][18] . The droplets of Ca may be found as the metal fog near the cathode 19,20) , when Ca dissolution rate is delayed.…”
Section: Reduction By Calciummentioning
confidence: 99%
“…[12][13][14] When pure Ca coexisted with CaCl 2 , TiO 2 was successfully reduced to -Ti with <1000 mass ppm oxygen only for 3.6 ks at 1173 K. 1) OS process uses the molten salt electrolysis to recycle CaO into Ca. Because of small solubility of Ca in CaCl 2 (about 4 mol%Ca at 1173 K [15][16][17][18] ), Ca formed near the cathode holds the high reducing ability. When TiO 2 is inserted in this region, it is reduced and recovered as metallic Ti.…”
Section: Introductionmentioning
confidence: 99%